130k views
3 votes
The x-y is the answer can someone please explain to me how to do

The x-y is the answer can someone please explain to me how to do-example-1
User Dparpyani
by
5.6k points

2 Answers

2 votes

Answer:

See picture.

Explanation:

The x-y is the answer can someone please explain to me how to do-example-1
User Adam Cataldo
by
5.3k points
4 votes

Answer:

Explanation:


(√(x-y))/(√(x+y)-√(x-y))-(√(x-y))/(√(x+y)+√(x-y))\\\\=(√(x-y)*(√(x+y)+√(x-y))-(√(x-y))*(√(x+y)-√(x-y)))/((√(x+y)-√(x-y))*(√(x+y)+√(x-y)))\\\\=\frac{√(x-y)*(√(x+y)+√(x-y)-√(x+y)+√(x-y))}{(√(x+y))^2-(\sqrt{x-y)^(2)}}\\\\=(√(x-y)*2√(x-y))/(x+y-x+y)\\\\=2*(x-y)/(2y)=(x-y)/(y)\\\\((√(x-y))/(√(x+y)-√(x-y))-(√(x-y))/(√(x+y)+√(x-y)))*y=(x-y)/(y)*y\\\\=x-y

User RLesur
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.